Placental Autophagy and Viral Replication Co-localize in Human and Non-human Primate Placentae Following Zika Virus Infection: Implications for Therapeutic Interventions - McKinney, Jennifer R.; Seferovic, Maxim D.; Major, Angela M.; Suter, Melissa A.; Tardif, Suzette D.; Patterson, Jean L.; Castro, Eumenia C. C.; Aagaard, Kjersti M. (Frontiers in Virology, 2021)
Background: Multiple studies have shown both induction and inhibition of autophagy during Zika virus (ZIKV) infection. While some have proposed mechanisms by which autophagic dysregulation might facilitate ZIKV vertical transmission, there is a lack of in situ data in human and non-human primate models. Given the paucity of pre-clinical data, we sought to assess cellular, spatial, and temporal associations between placental ZIKV infection and measures of autophagy in human primary cell culture and congenital infection cases, as well as an experimental non-human primate (NHP; marmoset, Callithrix jacchus) model. Methods: Primary trophoblast cells were isolated from human placentae (n=10) and infected in vitro with ZIKV. Autophagy-associated gene expression (ULK-1, BECN1, ATG5, ATG7, ATG12, ATG16L1, MAP1LC3A, MAP1LC3B, p62/SQSTM1) was then determined by TaqMan qPCR. In in vivo validation experiments, autophagy genes LC3B and p62/SQSTM1 were probed using in situ hybridization (ISH) in the placentae of human Congenital Zika Syndrome cases (n=3) and ZIKV-infected marmoset placenta (n=1) and fetal tissue (n=1). Infected and uninfected villi were compared for mean density and co-localization of autophagic protein markers. Results: Studies of primary cultured human trophoblasts revealed decreased expression of autophagy genes ATG5 and p62/SQSTM1 in ZIKV-infected trophoblasts (ATG5 fold change (±SD) 0.734-fold (±0.722), p=0.036; p62/SQSTM1 0.661-fold (±0.666), p=0.029). Histologic examination by ISH and immunohistochemistry confirmed spatial association of autophagy and ZIKV infection in human and NHP congenital infection cases. When quantified by densitometric data, autophagic protein LC3B and p62/SQSTM1 expression in marmoset placenta were significantly decreased in in situ ZIKV-infected villi compared to less-infected areas (LC3B mean 0.951 (95% CI, 0.930-0.971), p=0.018; p62/SQSTM1 mean 0.863 (95% CI, 0.810-0.916), p=0.024). Conclusion: In the current study, we observed that in the non-transformed human and NHP placenta, disruption (specifically down-regulation) of autophagy accompanies later ZIKV replication in vitro, in vivo and in situ. The findings collectively suggest that dysregulated autophagy spatially and temporally accompanies placental ZIKV replication. These studies have likely implications for both timing of therapeutics with ZIKV and other congenitally transmitted viruses, given the ubiquitous nature of autophagic disruption and dysregulation in host responses to viral infection during pregnancy.